The efficacy and safety of adjuvant immunotherapy after neoadjuvant immunotherapy combined with chemotherapy in locally advanced resectable esophageal squamous cell carcinoma: a real−world study - Wu, Xue; Ding, Fangjie; Bao, Shunshun; Mu, Yiming; Zhang, Jiandong; Zhang, Shuming; Hu, Pingping; Zhang, Yan; Liang, Ning; Deng, Guodong; Hao, Yuying; Liang, Xinquan; et al. (Frontiers in Immunology, 2025)
BackgroundThe promising therapeutic outcomes of neoadjuvant immunotherapy with chemotherapy (NAIC) in the treatment of resectable locally advanced esophageal squamous cell carcinoma (LA-ESCC) have been confirmed by several clinical trials. However, the potential benefits of adjuvant therapy for LA-ESCC patients remain unclear.Materials and methodsWe analyzed the LA-ESCC patients underwent NAIC and adjuvant immunotherapy between January 2020 and September 2023. The effectiveness and feasibility of adjuvant immunotherapy were evaluated.ResultsA total of 112 LA-ESCC patients were included. With a median follow-up of 24.0 months, all 112 patients had an R0 resection, and 23 patients (20.5%) achieved pathological complete response (pCR). The median disease-free survival (DFS) and overall survival (OS) were 18.5 and 24.0 months. The 12- and 24-month DFS rates were 91.0% and 81.7%, and the 12- and 24-month OS rates were 99.1% and 96.8%, respectively. Patients with BMI ≥20 kg/m2 had a longer 24-month DFS rate compared with those with BMI <20 kg/m2 (87.1% vs 62.0%, P=0.034). Additionally, patients with postoperative pCR than those with non-pCR achieved better 12-month (100% vs 88.6%) and 24-month (100% vs 77.3%, P<0.001) DFS. Superior DFS rates were acquired in patients with ypT0-1 (12-month: 98.1% vs 84.6%, P=0.008, 24-month: 95.4% vs 70.7%, P<0.001), ypN0 (12-month: 96.9% vs 83.1%, P=0.019, 24-month: 88.9% vs 72.2%, P=0.042), obtained T (12-month: 96.2% vs 78.3%, P=0.018, 24-month: 92.8% vs 56.0%, P<0.001) or TNM (12-month: 96.5% vs 84.8%, P=0.033, 24-month: 90.5% vs 72.5%, P=0.02) downstaging. A total of 85 (78.0%) patients experienced treatment-related adverse events (TRAEs), with the most common TRAEs were digestive reactions (52.3%) and neutropenia (50.4%). The majority of these events were classified as grade 1-2.ConclusionThe combination of NAIC and adjuvant immunotherapy displays short survival benefits and has an acceptable safety profile, which may be an effective treatment strategy for LA-ESCC patients.